Topical application of adenosine A2-type receptor agonists prevents contact hypersensitivity reactions in mice by affecting skin dendritic cells - Silva-Vilches, Cinthia; Bolduan, Vanessa; Alabdullah, Mohamad; Steinbrink, Kerstin; Probst, Hans Christian; Enk, Alexander; Mahnke, Karsten (The journal of investigative dermatology, 2023)
Adenosine (Ado) produced by skin and skin migratory CD73+ dendritic cells is critically involved in tolerance to haptens. We therefore investigated the use of Ado receptor agonists for the treatment of contact hypersensitivity reactions. A2A- 4-[2-[[6-Amino-9-(N-ethyl-β-D-ribofuranuronamidosyl)-9H-purin-2-yl]amino] ethyl]benzenepropanoic acid hydrochloride (CGS) and A2B- 2-[[6-Amino-3,5-dicyano-4-[4-[cyclopropylmethoxy]phenyl]-2-pyridinyl]thio]-acetamide (BAY) specific Ado receptor agonists were epicutaneously applied to the skin before sensitization and challenge with DNFB. Both agonists reduced ear swelling compared with solvent controls. This was accompanied by fewer activated T cells in the skin after the challenge and by higher numbers of T cells expressing anergic markers such as LAG-3, CD137, PD-1, CD272, and TIM-3 in the lymph nodes of CGS-treated groups. In ear tissue, Ado receptor agonist treatment reduced the production of proinflammatory cytokines and chemokines as well as the infiltration by neutrophils after sensitization. Moreover, reduced numbers of skin migratory dendritic cells producing less IL-12 and exhibiting lower expression of CD86 were recorded in lymph nodes after sensitization. In cocultures of skin migratory dendritic cells from CGS-treated mice with T cells, reduced proliferation of T cells and decreased secretion of proinflammatory cytokines compared with that of solvent controls were apparent. In conclusion, topical application of Ado receptor agonists to the skin prevents sensitization of T cells against haptens by reducing the migration and activation of skin migratory dendritic cells.
Online verfügbar 27. September 2022, Artikelversion 21. Februar 2023
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 21.04.2023